Reflexiones acerca de la brecha digital en la educación a distancia durante la pandemia de COVID-19 - Vertiz Manco, María Belén; Salas Oscco, Claudia Gisell (Pontificia Universidad Católica del Perú, 2021)
Within the context generated by an event with a global effect such as the current COVID-19 pandemic, it can be asserted that –along with the adequate provision of basic needs for human survival– education is one of the factors of daily life to which the greatest concentration for preserving is dedicated. In this sense, there is a considerable advantage: an alternative methodology to the coexistence of teachers and students in a common physical space, which, although it was not an option for general application, was not completely alien to the average student in a country like Peru. We refer to long-distance education. However, while the immediate benefits of adopting this system, at first glance so accessible, are in fact many, the untimely imposition of long-distance education at all educational levels in the country was not established without challenges or setbacks. The widening of the digital gap –once a relatively passive reality to ignore for those who did not perceive themselves as particularly affected by it– reached new heights with breakneck speed and became a major concern due to its effect on the ability of Peruvian students to continue receiving their instruction under the virtual modality, or, failing that, to make visible in a forceful way the effects of the increasingly acute social inequality that harms the country.

Dentro del contexto generado por un acontecimiento de efecto global como lo es la actual pandemia de COVID-19, se puede aseverar que –junto con el adecuado aprovisionamiento de las necesidades básicas para la supervivencia humana– la educación es uno de los factores de la cotidianidad a los que se les dedica mayor concentración por preservar. En ese sentido, puede contarse con una considerable ventaja: la existencia de una metodología alternativa a la coexistencia de maestros y alumnos en un espacio físico común, que, si bien no constituía una opción de aplicación generalizada, tampoco resultaba completamente ajena al estudiante promedio en un país como el Perú. Nos referimos a la educación a distancia. Sin embargo, mientras que los beneficios inmediatos de adoptar este sistema, a primera vista tan accesible, de hecho, son muchos, la imposición intempestiva de la educación a distancia en todos los niveles educativos en el país no se instauró sin retos ni reveses. La ampliación de la brecha digital antes una realidad relativamente pasiva de ignorar para aquellos que no se percibían como especialmente afectados por esta– alcanzó nuevas alturas con una velocidad vertiginosa, y se convirtió en una preocupación de suma relevancia debido a su efecto sobre la habilidad de los estudiantes peruanos de continuar recibiendo su instrucción bajo la modalidad virtual o en su defecto, por visibilizar de manera contundente los efectos de la cada vez más aguda desigualdad social que perjudica al país.
Reflections on the digital gap in long-distance education during the COVID-19 pandemic
Keywords: Brecha digital; Educación; Educación a distancia; TIC; Pandemia; https://purl.org/pe-repo/ocde/ford#5.04.01